Studies on sources of potassium on growth, yield and economics of groundnut (Arachis hypogaea L.): STUDIES ON SOURCES OF POTASSIUM ON GROWTH, YIELD AND ECONOMICS OF GROUNDNUT - A ABIRAMI,; R SANKAR,; U BAGAVATHI AMMAL,; P SARAVANANE, (Journal of Oilseeds Research, 2026)
A field experiment was conducted at Earipakkam village, Puducherry to evaluate the effect of different potassium sources on growth, yield and economics of groundnut variety G-7. The experiment was laid out in Randomized Block Design with eight treatments and three replications. Treatments included different combinations of muriate of potash (MOP), wood ash, and potash-solubilizing bacteria (KSB) with varying potassium levels. Results revealed that application of 75% K through MOP + 25% K through wood ash + potash-solubilizing bacteria significantly enhanced plant height (45.6 cm), number of branches (18.6), leaf area index (3.59), nodules per plant (77.7), pod yield (37.70 q/ha), gross return and B:C ratio.